Analisis modifikasi sistem kopling otomatis ke sistem kopling manual terhadap akselerasi sepeda motor Supra-X tahun 2014 - I Nyoman Sutarna; I Nengah Ludra Antara; I Ketut Suherman; I Ketut Adi (Journal of Applied Mechanical Engineering and Green Technology, 2022)
Acceleration is the change in speed in a certain unit of time. The method applied in this research is the experimental method. The purpose of the analysis of the modification of the automatic clutch system to the manual clutch system on motorcycle acceleration is to determine the results of the modification of the automatic clutch system to the manual clutch system on acceleration. The results of the first test showed that the average acceleration in the automatic clutch system was 101.05 m/s2, and the second an average acceleration was 101.14 m/s2, so the average acceleration was 101.095 m/s2. When using the manual clutch system, the first test results obtained an average acceleration of 77.87 m/s2, the second obtained an average acceleration of 78.51, so the average acceleration was 78.19 m/s2. So the average acceleration using the automatic clutch system is 101,095 m/s2, while those using the manual clutch system are 78.19 m/s2. There was a very significant difference of 101.095 m/s2 - 78.19 m/s2 = 22,905 or 22.65%. This means the use of the manual clutch system accelerates faster than the automatic clutch system.